17.3L: Late‐News Paper: Enhancing the Contrast Ratio of Blue Phase LCDs. Issue 1 (1st July 2013) - Liu, Yifan; Lan, Yi‐fen; Zhang, Hongxia; Zhu, Ruidong; Xu, Daming; Tsai, Cheng‐Yeh; Lu, Jen‐Kuei; Sugiura, Norio; Lin, Yu‐Chieh; Wu, Shin‐Tson
Abstract Experimental evidence proves that polymer‐stabilized blue phase liquid crystal is not perfectly optically isotropic. The optical rotatory power (ORP) of double twist cylinders causes the polarization axis of the transmitted light to rotate a small angle, and leaks through the crossed polarizers. Rotating the analyzer by ∼2o to correct this ORP can improve the contrast ratio by 3X.